Atomic‐Scale Determination of Active Facets on the MoVTeNb Oxide M1 Phase and Their Intrinsic Catalytic Activity for Ethane Oxidative Dehydrogenation. Issue 31 (16th March 2016) - Melzer, Daniel; Xu, Pinghong; Hartmann, Daniela; Zhu, Yuanyuan; Browning, Nigel D.; Sanchez‐Sanchez, Maricruz; Lercher, Johannes A.
Abstract: Aberration‐corrected high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) has been used to image the basal {001} plane of the catalytically relevant M1 phase in MoVTeNb complex oxides. Facets {010}, {120}, and {210} are identified as the most frequent lateral termination planes of the crystals. Combination of STEM with He ion microscopy (HIM) images, Rietveld analysis, and kinetic tests reveals that the activation of ethane is correlated to the availability of facets {001}, {120}, and {210} at the surface of M1 crystals. The lateral facets {120} and {210} expose crystalline positions related to the typical active centers described for propane oxidation. Conversely, the low activity of the facet {010} is attributed to its configuration, consisting of only stable M6 O21 units connected by a single octahedron. Thus, we quantitatively demonstrated that differences in catalytic activity among M1 samples of equal chemical composition depend primarily on the morphology of the particles, which determines the predominant terminating facets. Abstract : Surface structures : High‐angle annular dark‐field scanning transmission electron microscopy analysis provided an atomic level description of the termination of M1 phase crystals of MoVTeNbOx catalysts. The statistical analysis of electron microscopy images combined with reaction kinetics allowed identification of those crystalline facets active in ethane oxidative dehydrogenation.